Perceptions towards a healthy diet among a sample of university people in Portugal. Issue 4 (30th April 2018) - Ferrão, Ana Cristina; Guiné, Raquel P.F.; Correia, Paula; Ferreira, Manuela; Cardoso, Ana Paula; Duarte, João; Lima, João
Abstract : Purpose: A healthy diet has been recognized as one of the most important factors associated with maintaining human health and helping in preventing the development of some chronic diseases. Therefore, this paper aims to study the perceptions of a sample of university people regarding a healthy diet. Design/methodology/approach: It was undertaken a descriptive cross-sectional study on a non-probabilistic sample of 382 participants. The data were collected among a sample of Portuguese university people and measured whether people's perceptions were compliant with a healthy diet. Findings: The results revealed that the participants' perceptions were, in general, compliant with a healthy diet (scores between 0.5 and 1.5, on a scale from −2 to +2). However, significant differences were found between age groups ( p = 0.004), with a higher average score for young adults, and also between groups with different levels of education ( p = 0.025), with a higher score for university degree. The variable chronic diseases also showed significant differences ( p = 0.017), so that people who did not have any chronic diseases obtained a higher score. Originality/value: This study is considered important because it provides evidences about the relation between nutrition knowledge and the perceptions towards a healthy diet. The study allowed concluding that the participants were aware about some nutritional aspects of their diets and, therefore, their perceptions were compliant with a healthy diet. This finding is very relevant because it could be a support for health policy initiatives directed at promoting healthy eating behaviours.